International regulation of commercially exploited sharks - Schatz, Valentin; Kachelriess, Daniel (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2026)
This article examines the obligations of States under international fisheries law with respect to the conservation and management of oceanic sharks caught incidentally in fisheries under the competence of regional fisheries management organizations with a mandate to manage tuna and tuna-like species (t-RFMOs). It argues that, in certain t-RFMO-managed fisheries, specific commercially exploited shark species should be legally classified as (secondary) target stocks rather than non-target species under the United Nations Convention on the Law of the Sea, the Agreement for the Implementation of the Provisions of the United Nations Convention on the Law of the Sea of 10 December 1982 relating to the Conservation and Management of Straddling Fish Stocks and Highly Migratory Fish Stocks and other instruments of international fisheries law. It follows that t-RFMOs have a responsibility to manage such populations of commercially exploited sharks within their regulatory competence through precautionary, science-based, and effective conservation and management measures (CMMs). All t-RFMOs already have a competence to adopt CMMs with respect to commercial shark fisheries insofar as they are incidental to fisheries covered by the primary competence of the respective t-RFMOs, such as tuna. That said, our analysis of t-RFMO practice shows that t-RFMOs have not yet adequately fulfilled their responsibility to regulate commercially exploited sharks through effective CMMs, such as precautionary reference points, harvest strategies (including, but not limited to, harvest control rules), total allowable catches and retention limits.
Challenging the notion of shark “bycatch” in tuna RFMOs
Keywords: Commercial Shark Fisheries; Conservation And Management Measures; Bycatch; Regional Fisheries Management Organizations (RFMOs)